Development of a counselling-based self-wellbeing model for informal caregivers of childhood cancer patients in Malaysia - Mat Rani, Nurul Hasyimah; Daud, Nurul ‘Ain Mohd; Yusof, Hapsah Md; Zaini, Syaza Hazwani; Kee, Pau; Yasim, Mazuki Mohd; Ismayatim, Wan Faizatul Azirah; Sansuddin, Nur Shuhana Mohd (Institute of Advanced Engineering and Science, 2025)
Cancer is a chronic disease that causes patients and their caregivers to face various challenges throughout treatment and care. This study aimed to develop a counselling-based self-wellbeing model for informal caregivers of childhood cancer patients in Malaysia. This study employed the design and development research (DDR). The first phase involved needs analysis using a systematic literature review and semi-structured interviews of nine caregivers of childhood cancer. The second phase involved two methods: nominal group technique (NGT) and interpretive structural modeling (ISM). The third phase involved evaluating the usability of the model through the Fuzzy Delphi method (FDM) with the agreement of seven experts. This study successfully developed a counselling-based self-wellbeing model for informal caregivers of childhood cancer patients in Malaysia. This model has 12 components consisting of: i) financial; ii) career; iii) knowledge related to management and care of child cancer patients; iv) emotional management and care; v) spiritual; vi) cognitive and rationalization; vii) social relationships; viii) roles of counsellors in helping parents; ix) spouse and family relationships; x) physical; xi) communication; and xii) facilities. This model is proposed to be used by counsellors, especially who serve in health institutions to help parents who have children with cancer.